Magnus Chase and the Ship of the Dead (Book 3) - Rick Riordan (London Puffin Books, 2017)
Loki the trickster god is free from his chains. Now he's readying Naglfar, the Ship of the Dead, armed with a host of giants and zombies, to sail against the Norse gods and begin the final battle of Ragnarok. It's up to Magnus Chase and his friends to stop Loki's plans, but to do so they will have to sail across the oceans of Midgard, Jotunheim and Niflheim in a desperate race to reach Naglfar before it's ready to sail on Midsummer's Day. Along the way, they will face angry sea gods, hostile giants, and an evil fire-breathing dragon who happens to be a former acquaintance. But Magnus's biggest challenge will be facing his own inner demons. To defeat Loki, Magnus will need to use words, not force. This will require finding a magical elixir so deadly that it will either make Magnus Chase powerful enough to out-talk the silver-tongued Loki, or destroy Magnus utterly.